(اﻟﻌﺷق اﻹﻟﮭﻲ ﻓﻲ اﻟﻣﺻﺎدر اﻷدﺑﯾﺔ (ﺑﺣث ﻣﺳﺗل ﻣن اطروﺣﺔ دﻛﺗوراه - أ.د .ﺣﻣﯾدة ﺻﺎﻟﺢ اﻟﺑﻠداوي م.د. ﺟﻧﺎن ﻗﺣطﺎن ﻓرﺣﺎن (College of Education for Women, 2019)
Passion as as impulse nas not reached the imporhance it dessryes in acabemic stubies desse its essence literatyre lt reprt ot the pillars of arab of ayab coyrtship lt has close connection to hn man life and destiny thus we think that it nee ds analysis and follow regardless of the various studies that history preserved dealing with an area reguires great tot it one widespresad and literary issues lt rises and theme of love and passion whether in hints or in details.